Salivary markers of hepato-metabolic comorbidities in pediatric obesity. Issue 4 (April 2019) - Troisi, Jacopo; Belmonte, Federica; Bisogno, Antonella; Lausi, Olga; Marciano, Francesca; Cavallo, Pierpaolo; Guercio Nuzio, Salvatore; Landolfi, Annamaria; Pierri, Luca; Vajro, Pietro
Abstract: Background: The pediatric obesity epidemic calls for the noninvasive detection of individuals at higher risk of complications. Aims: To investigate the diagnostic role of combined salivary uric acid (UA), glucose and insulin levels to screen noninvasively for metabolic syndrome (MetS) and nonalcoholic fatty liver disease. Methods: Medical history, clinical, anthropometric, and laboratory data including serum triglyceride, glucose, insulin, HOMA, HDL-cholesterol, and UA levels of 23 obese children (15 with [St+] and 8 without [St−] ultrasonographic hepatic steatosis) and 18 normal weight controls were considered. Results: Serum and salivary UA (p < 0.05; R 2 = 0.51), insulin (p < 0.0001; R 2 = 0.79), and HOMA (p < 0.0001; R 2 = 0.79) levels were significantly correlated; however their values tended to be only slightly higher in the obese patients, predominately in [St+], than in the controls. Notably, UA and insulin levels in both fluids increased in parallel to the number of MetS components. After conversion of the z-logit function including salivary/anthropometric parameters in a stepwise logistic regression analysis, a factor of 0.5 allowed for predicting hepatic steatosis with high sensitivity, specificity, and total accuracy. Conclusions: Salivary testing together with selected anthropometric parameters helps to identify noninvasively obese children with hepatic steatosis and/or having MetS components.